Communication Apprehension in English Learners and its Impact on their Motivation - Saira Rahman,; Hazrat Umar, (JCTE, 2024)
Learners who experience communication apprehension may try to avoid interpersonal interactions, hampering the language learning process. This experience may hinder learners from performing well in any communicative setting. This study examines communication apprehension (CA) in learners when they speak the English language in classes focusing on speaking and investigates the influence of fear of communication on the learners’ motivation. The sample consists of 350 diploma students studying English and 60 English teachers teaching diploma courses. Qualitative data included semi-structured interviews, and quantitative came from a questionnaire. The quantitative data were analyzed using SPSS, while the qualitative data were analyzed thematically. Regression and correlation analyses were performed to determine the effect of CA on learners’ motivation. The results showed that communication apprehension exists in learners and affects their motivation significantly, which may slow down their communication skills development. This study has implications for teacher preparation and teacher training in the intersection between motivation and oral skills development.